Reducing poverty through fiscal decentralization in Ghana and beyond: A review - Williams Agyemang-Duah; Evans Kafui Gbedoho; Prince Peprah; Francis Arthur; Augustus Kweku Sobeng; Joshua Okyere; Jennifer Mengba Dokbila (Cogent Economics & Finance, 2018)
The unfinished agenda in the theory and practice of fiscal decentralization is how fiscal decentralization affects the universal plague of poverty reduction in developing economies. Focusing on developing economies especially Ghana, and also employing secondary sources of information, this papermade an attemptto provide a holistic review of the concept of fiscal decentralization and its effects on poverty reduction from the optimist and pessimist views. The paper affirmed that fiscal decentralization has the potential for poverty reduction when it is characterized by greater financial autonomy of the local units with proper budgetary allocation, prioritization, accountability and responsiveness. Accountability and proper regulation may reduce some institutional setbacks such as corruption from the system. We, therefore, recommended for a more effective, efficient, and transparent institutional and legal framework to ensure effective fiscal transfer between the central and local governments in order to eliminate various lapses associated with fiscal decentralization as highlighted by the pessimists.
Keywords: 330; fiscal decentralization; poverty reduction; optimist view; pessimist view; developing economies; Ghana